Modem Electronic Music: Breaking Down the Producer/Consumer Dichotomy - Kane, Anne-Marie (My University, 2007)
This thesis investigates how modern technology, such as the internet and computer software, has deconstructed the traditional relationship between the music consumer and the music producer/maker. The internet, in particular, has facilitated the production and distribution of music to a potentially world-wide audience without using the traditional avenues offered by the recording industry. Advancements in computer software have also enabled the amateur composer to write and record music without the knowledge, experience and tools utilized by the professional composer or songwriter. The resulting style of music composed by using this software is electronic popular music and many parallels can be drawn to the history of modernist electronic music. To explore this, I have conducted interviews with people from different parts of the world who are currently active in composing and distributing music using the Internet. These amateur composers also use computer software to facilitate the production of their music without using traditional means. Drawing parallels between postmodernist theories and the success of their projects and personal experiences demonstrates the breaking down of the producer/consumer dichotomy.
Keywords: Arts and Humanities; Arts and Humanities